A Parallel World for the World Bank: A Case Study of Urgent: Evoke, An Educational Alternate Reality Game - Waddington, David (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2013)
In 2010, the World Bank launched Urgent: Evoke, an alternate reality game. Conceived in response to the demands of African universities, the game was designed to promote the World Bank Institute’s vision of positive global change through social innovation, and made substantial use of Web 2.0 tools such as blogs, personal profiles, and social networks. This article offers a case study of Urgent: Evoke, divided into four sections: first, the potential to use video games as citizenship education tools is discussed; second, the unique game genre (alternate reality games) into which Evoke falls is explained and some possible uses of this genre in higher education are examined; third, the functioning of the Evoke game world is explained; and fourth, the results of the Evoke educational project are assessed. The case study concludes with some commentary on Evoke’s ideological message, which those less sympathetic to capitalism may view as problematic.